Cross-Border Printing Privileges in the Seventeenth-Century Low Countries - Nina Lamal (Early Modern Low Countries)
Based on the assumption that printing privileges were meant to protect printer-publishers from market competition locally, scholars have primarily studied such privileges in individual states. This article is the first attempt to study printing privileges transnationally, by focusing on the phenomenon of cross-border printing privileges in the seventeenth-century Habsburg Netherlands and the Dutch Republic. I examine both the foreign printers requesting a privilege in the Low Countries and local printers requesting a privilege from a foreign authority. In doing so, this essay analyses why printers were requesting privileges for their books from more than one authority across political borders. Rather than seeing these cross-border privileges solely as a way for printers to expand the reach and commercial viability of their published works, this article demonstrates that, by securing privileges from multiple authorities, printers showed they were able to navigate the market for institutions and complex networks of power. By analysing diplomatic correspondence alongside privilege requests, I demonstrate the crucial role of ambassadors in favouring certain printers and their project. Throughout the seventeenth century, the state and its representatives became involved in securing such privileges from other authorities. This hitherto hidden role of diplomatic agents alerts us both to the fierce competition in a certain segment of the international book market and the importance of managing a state’s international reputation.